Shrub Growth, NPP, and Nitrogen Assimilation for Two Years in an Alberta Peatland Subjected to Increasing Nitrogen Deposition, 2014-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). In July of each year, we collected new growth of the three shrub species, returned them to the lab, and analyzed them. Non-destructive measurement of aboveground NPP for the three dominant shrub species, Andromeda polifolia , Chamaedaphne calyculata , and Rhododendron groenlandicum was based on allometric equations developed. Results for species were varied, however, water addition alone had no significant effect on NPP for any of the species or for the dominant shrubs combined in either 2014 or 2015 (p >= 0.47). The mass of newly produced shoot segments for Chamaedaphne calyculata , Andromeda polifolia , Rhododendron groenlandicum , and these three dominant shrubs combined all increased with increasing N input. As N input increased, the number of newly produced shoots (vegetative buds m -2 ) increased linearly for A. polifolia and the three shrub species combined. The number of newly produced shoots increased up to 16.6 ± 2.5 kg N ha -1 yr -1 and then decreased for C. calyculata and was unaffected for R. groenlandicum . Shrub growth response to increased N could lead to a shading out of the underlayer of mosses changing the bog and potentially compromising its structure and function.